1997
DOI: 10.1183/09031936.97.10122898
|View full text |Cite
|
Sign up to set email alerts
|

Pleural effusion during bromocriptine exposure in two patients with pre-existing asbestos pleural plaques: a relationship?

Abstract: P Pl le eu ur ra al l e ef ff fu us si io on n d du ur ri in ng g b br ro om mo oc cr ri ip pt ti in ne e e ex xp po os su ur re e i in n t tw wo o p pa at ti ie en nt ts s w wi it th h p pr re e--e ex xi is st ti in ng g a as sb be es st to os s p pl le eu ur ra al l p pl la aq qu ue es s: : a a r re el la at ti io on ns sh hi ip p? ? ABSTRACT: Two patients with pleural plaques developed pleural effusion and subsequent diffuse pleural fibrosis 50 and 39 yrs after their first exposure to asbestos. The diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In 1997, two independent reports were published, one of 11 Swedish and 4 Australian cases (1) and one of 2 patients from The Netherlands (2). Four of the eleven Swedish cases were reported to the registry and are thus included in our present study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In 1997, two independent reports were published, one of 11 Swedish and 4 Australian cases (1) and one of 2 patients from The Netherlands (2). Four of the eleven Swedish cases were reported to the registry and are thus included in our present study.…”
Section: Discussionmentioning
confidence: 96%
“…A rare, but well-known side effect of these drugs is pleuropulmonary reactions. A few years ago, it was suggested that this particular side effect occurs more commonly in persons earlier exposed to asbestos (1,2), which is also well known to cause lesions of both the pleura and the lung parenchyma. To investigate this intriguing connection between an occupational exposure and a drug given for medical reasons further, we decided to investigate all reports on the pleuropulmonary side effects of the ergot drugs used in Sweden in the Swedish Side Effect Registry.…”
mentioning
confidence: 99%
“…As we feel from the papers cited above [2,3], and from our ongoing personal experience with further cases (unpublished), bromocriptine-induced loss of lung function is quite aggressive and, more often than not, recovers only partially after the drug has been stopped. The resulting permanent impairment in lung function is likely to bring such patients to Boards of Compensation for Occupational Lung Diseases, and a common attitude is desirable.…”
Section: Asbestos Ergot Drugs and The Pleuramentioning
confidence: 99%
“…Our recent editorial [1] commenting on the paper by KNOOP et al [2] and HILLERDAL et al [3] discussed mainly clinical and aetiological issues regarding the possible interaction between former asbestos exposure and intake of ergot drugs in the pathogenesis of subacute pleural effusions or thickening. As the ultimate outcome of pleural effusions or thickening following treatments with bromocriptine in former asbestos workers becomes more clear, issues related to charges against prior occupational exposure and attending compensation will need to be considered in more depth.…”
Section: Asbestos Ergot Drugs and The Pleuramentioning
confidence: 99%
See 1 more Smart Citation